IMPROVING STUDENTSâ SPEAKING SKILL THROUGH TALKING STICK - Romlah, Siti (Research And Innovation In Language Learning (RILL), 2018)
This classroom action research was aimed at improving studentsâ speaking skill on trascational/interpersonalof class VII A SMP Negeri1 Kedawung Kabupaten Cirebon through Talking Stick.Â  The classroom actionÂ  research used Kemmis and Taggart cycle model ith 4 stages.Â  The subject of the research as tudents of class VIIA with 43 students.Â  The research as carried out from September- November 2015 withÂ  2 cycles. The technique of data collection were performance test, kerja, while for collecting teacherâ perfomance used observationÂ  and for collecting the data of studentsâs responses used questioner. To analize data, data reduction-percentage- and simple calculation, data presentation , intrepretation. Â The result showed that in general there was an improvement of classical learning mastery of students; speaking skill of trasactionl/interpersonal text about 35,36%. Â This was done by comparing each test on each treatment. The result of cycle 1 showed 19 students of VII A reached classical mastery of learning for about Â 79,54%. Â The average score of cycle 1 was 79 and the average score 2 was 81 with very good category.Â  The data of studentsâ respondÂ  reached active criteria on cycle 1 and very good criteria on cycle 2. Â The teacherâs performance reached score 72 on cycle 72 with very good criteria, and 89 on cycle 2 with very good criteria.Â  Based on the gained data, it can be said that the reserach had achieved its target and the improvement of studentsâ speaking skill on trascationl/interpersonal text of class VII A of SMP Negeri 1 Kedawung kabupaten Cirebon through Talking Stick was succesfull.